The burden of liver cancer in Mongolia from 1990–2019: a systematic analysis for the Global Burden of Disease Study 2019 - Batsaikhan, Oyundari; Chimed-Ochir, Odgerel; Kubo, Tatsuhiko; Jigjidsuren, Chinburen; Delgermaa, Vanya; Purevdagva, Anuzaya; Sarankhuu, Amarzaya; Nansalmaa, Erdenekhuu; Tsegmed, Uranchimeg; Davgasuren, Badral; Purev, Oyuntsetseg; Mokdad, Ali H.; et al. (Frontiers in Oncology, 2024)
Background: Liver cancer remains the leading cause of death and public health threat among the Mongolian population. Methods: We extracted the primary liver cancer data from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2019 to examine the mortality and morbidity of liver cancer by its etiological types, including alcohol, viral hepatitis B and C, and non-alcoholic steatohepatitis (NASH). The data was extracted by sex and 5-year age intervals from 1990 to 2019. Data included mortality, incidence, years of life lost (YLLs), years lived with disability (YLDs), and disability-adjusted life-years (DALYs) of liver cancer among the Mongolian population. Results: Mongolia had the world's highest age-standardised DALYs for liver cancer (2558.1) in 2019. Alcohol-attributable DALYs (786.6) were 29 times higher than the global average (26.1), and liver cancer due to hepatitis C (752.6) and B (763.2) were 21.5 (35.0) and 10.9 (69.1) times higher, respectively. There has been a steady increase in the incidence and number of deaths caused by liver cancer in Mongolia. In 2019, liver cancer incidence due to alcohol consumption was 3.1 times higher for males than females, and hepatitis B was 2.7 times higher for males than females. However, the incidence of hepatitis C and NASH was slightly higher for females. Deaths from liver cancer accounted for 9.51% (2365) of total deaths in 2019, with a continuously increasing trend in the fraction of deaths compared to 1990, which was 11 times higher than the global average (0.86%), particularly in females with a 319.6% (95% UI 234.9-435.7) increase observed. Liver cancer due to hepatitis B, C, and alcohol each shared about one-third of liver cancer deaths. Conclusion: A comprehensive analysis of the liver cancer burden in Mongolia reveals alcohol use and viral hepatitis as primary causes of liver cancer mortality, significantly impacting the disease burden. Although significant milestones have progressed, addressing the unique demographic and geographical challenges requires tailored approaches for specific target populations. The evidence generated from this analysis is crucial to support policy guidance, contribute to evidence-based decisions, guide public health prevention measures, and amplify population health promotion and disease prevention throughout Mongolia.